2022
DOI: 10.3310/nihropenres.13290.1
|View full text |Cite
|
Sign up to set email alerts
|

Remote care in UK general practice: baseline data on 11 case studies

Abstract: Background: Accessing and receiving care remotely (by telephone, video or online) became the default option during the coronavirus disease 2019 (COVID-19) pandemic, but in-person care has unique benefits in some circumstances. We are studying UK general practices as they try to balance remote and in-person care, with recurrent waves of COVID-19 and various post-pandemic backlogs. Methods: Mixed-methods (mostly qualitative) case study across 11 general practices. Researchers-in-residence have built relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The current authors’ own ongoing empirical research has begun to identify similar findings among GPs and their support staff. 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current authors’ own ongoing empirical research has begun to identify similar findings among GPs and their support staff. 27 …”
Section: Discussionmentioning
confidence: 99%
“…A qualitative of 40 UK GPs conducted in 2020-2021 (25), and a social media analysis of GPs' postings during the pandemic by the same authors (26), both found that negative media portrayals of general practice (especially the implication that practices were closed when the reality consisted of long hours and high workload) were a significant factor contributing to low morale. Our own ongoing empirical research has begun to identify similar findings among GPs and their support staff (27).…”
Section: Implications For Research and Practicementioning
confidence: 90%
“…We have collected and analysed baseline data on all practices, which we have presented in a separate paper 102 .…”
Section: Study Statusmentioning
confidence: 99%
“…We have collected and analysed baseline data on all practices, which we have presented in a separate paper 102 . Selected additional data on this ongoing, mainly qualitative study will be made available to researchers on reasonable request to the lead author (TG).…”
Section: Ethics and Disseminationmentioning
confidence: 99%
“…It combines research interviews and ethnography in 11 GP practices across the UK, along with patient learning sets and action-orientated research workshops. This small sample represents the range of triage and appointment booking options currently offered: some allow patients to choose their appointment type, some use online and telephone triage, and some operate a “telephone first” system 10. Early findings from this study suggest some avenues for improving safety.…”
mentioning
confidence: 99%